PIDANA TERHADAP PARA PENYELEWENGAN DANA DESA - Dikir Dakhi (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to determine the Criminal Liability of Village Fund Misappropriation. In Decision Number 27 / Pid.Sus-TPK / 2018 / PT MDN. The type of research used is Normative Research, by examining various kinds of formal legal rules such as laws, literature, namely primary data, secondary data, tertiary data. The data analysis used was qualitative, an effort made by working with data and describing it. Based on the results of research and discussion: the imposition of criminal acts of corruption Decision Number 27 / Pid.Sus-TPK / 2018 / PT MDN using Article 2 Jo Article 18 Law Number 31 Year 1999 concerning Eradication of Corruption Crimes as amended and added to the Law Law Number 20 of 2001 concerning Eradication of Corruption in conjunction with Article 55 paragraph (1) 1 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law and other legal provisions, as well as the imposition of case fees in both levels of the judiciary which are at the level of the appeal as stated in the ruling of the decision is in accordance with and fulfills the elements of the criminal act in that article.